Segmenting beyond behavioural intentions: Fine tuning music festival visitors' music appreciation. Issue 2 (5th June 2017) - Kruger, Martinette; Saayman, Melville
Abstract : Purpose: The purpose of this paper is to determine whether a music festival leads to additional intangible benefits such as the appreciation of the specific music genre and music tourism. This was done by using visitors' behavioural intentions related to these benefits as a tool for market segmentation. Design/methodology/approach: The research followed a quantitative approach by conducting a visitor survey at an international jazz festival in South Africa. Findings: The results showed that visitors' post-festival behavioural intentions are a useful market segmentation tool. This approach revealed three distinct market segments with different levels of post-festival behavioural intentions (high, medium, and low). The results further showed that music festivals have the potential to create benefits beyond the festival itself or the host destination in the form of music tourism and the appreciation of a music genre. However, influencing visitors' behavioural intentions can only be achieved by a thorough understanding of the characteristics of the market. Originality/value: This research applied an innovative market segmentation approach that showed the post-festival behavioural intentions of different visitor segments at a music festival. The findings confirm that music festivals can have far-reaching benefits that can contribute to their legacy.